Effectiveness and Feasibility of Virtual International Exchange Program for Occupational Therapy Students to Develop International Perspective and Professional Skills: A Mixed-Method Study - Suyama, Natsuka; Inoue, Kaoru; Sahid, Muhammad Hidayat; Sasaki, Chihiro; Shioji, Rieko (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2024)
Background: Virtual international exchange programs have been promoted; however, the effectiveness of the programs has not yet been examined well in the field of occupational therapy (OT) field. This study aimed to examine the effectiveness and feasibility of a virtual international exchange program for OT students.Methods: Mix-method was applied in this study.Two universities from Japan and Indonesia created an exchange program to cultivate international perspectives and facilitate gaining OT professional knowledge and skills, as well as learning basic scientific study skills. Questionnaires on international minded and program evaluations, which were analyzed by descriptive analysis, were given to the participants before and after the program. Focus group interviews, which were analyzed with reflective thematic analysis, were conducted after the program.Results: Ten students joined the program, six students answered the questionnaires, and eight students participated in the focus group interviews. Students were satisfied with the program overall, even though there were no significant changes in the total scores of the international minded between before and after the program. In the focus group interviews, the participants mentioned their motivations for participating in the program, program evaluation, international minded, and self-growing awareness. The participants expressed that they gained OT professional knowledge and academic skills from the program.Conclusion: As a feasible virtual program, well-organized programs considering the students’ academic learning skills and interests could provide opportunities for individual development, acquiring professional knowledge, and incite self-growing. In addition, the result might show the effectiveness of virtual programs to cultivate international perspective and professional knowledge.